ENDOMETRIAL CELLS APOPTOSIS IN HEALTH AND PROLIFERATIVE DISEASES OF THE UTERUS - N. V. Borovkova; M. M. Damirov; O. N. Oleynikova (Неотложная медицинская помощь, 2016)
The article presents the literature data on the regulation of endometrial cells apoptosis in health and proliferative diseases of the uterus. It is noted that throughout the menstrual cycle the cells apoptosis and regeneration take place in strictly controlled sequence and depend on the phase of the cycle and hormonal changes. The expression of Bcl-2 (inhibitor of apoptosis) in cells also varies cyclically in endometrial glandular cells, peaking in the late proliferative phase, and then decreasing to a minimum at the end of the secretory phase and within the menstruation phase. In endometriosis, the apoptosis index in endometrial functional layer is significantly lower than in healthy women. The weakened apoptosis is associated with the disturbance of its regulation. The expression of Bcl-2 increased with the progress of the disease in the endometrial tissue, while the expression of bax (apoptosis activator) corresponded to figures in healthy women. The increase in the expression of Bcl-2 was observed in the cells of myomatous fibroids. Thus, in patients with uterine myoma the ratio Bcl-2/Bax is more important. It is noted that the weakened apoptosis of endometrial cells and disorders of apoptosis regulation are leading pathogenic mechanisms for the development of proliferative diseases of the uterus. This is the basis of a new search for the effective diagnosis, prognosis and treatment of this widespread disease.